Tai Chi Chuan for Cardiac Rehabilitation in Patients with Coronary Arterial Disease - Nery,Rosane Maria (2014)
Background:Several studies have shown that Tai Chi Chuan can improve cardiac function in patients with heart disease.Objective:To conduct a systematic review of the literature to assess the effects of Tai Chi Chuan on cardiac rehabilitation for patients with coronary artery disease.Methods:We performed a search for studies published in English, Portuguese and Spanish in the following databases: MEDLINE, EMBASE, LILACS and Cochrane Register of Controlled Trials. Data were extracted in a standardized manner by three independent investigators, who were responsible for assessing the methodological quality of the manuscripts.Results:The initial search found 201 studies that, after review of titles and abstracts, resulted in a selection of 12 manuscripts. They were fully analyzed and of these, nine were excluded. As a final result, three randomized controlled trials remained. The studies analyzed in this systematic review included patients with a confirmed diagnosis of coronary artery disease, all were clinically stable and able to exercise. The three experiments had a control group that practiced structured exercise training or received counseling for exercise. Follow-up ranged from 2 to 12 months.Conclusion:Preliminary evidence suggests that Tai Chi Chuan can be an unconventional form of cardiac rehabilitation, being an adjunctive therapy in the treatment of patients with stable coronary artery disease. However, the methodological quality of the included articles and the small sample sizes clearly indicate that new randomized controlled trials are needed in this regard.